2016
DOI: 10.1037/a0039758
|View full text |Cite
|
Sign up to set email alerts
|

Caveats for the spatial arrangement method: Comment on Hout, Goldinger, and Ferguson (2013).

Abstract: The gold standard among proximity data collection methods for multidimensional scaling is the (dis)similarity rating of pairwise presented stimuli. A drawback of the pairwise method is its lengthy duration, which may cause participants to change their strategy over time, become fatigued, or disengage altogether. Hout, Goldinger, and Ferguson (2013) recently made a case for the Spatial Arrangement Method (SpAM) as an alternative to the pairwise method, arguing that it is faster and more engaging. SpAM invites p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(57 citation statements)
references
References 56 publications
7
50
0
Order By: Relevance
“…According to Hout et al (2013), the resolution that typical Likert scales offer is too limited for participants to convey their similarity perceptions. 1 Despite these concerns, average similarity data obtained with PRaM tend to be reliable (Bijmolt & Wedel, 1995;Giordano et al, 2011;Verheyen et al, 2016).…”
Section: Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Hout et al (2013), the resolution that typical Likert scales offer is too limited for participants to convey their similarity perceptions. 1 Despite these concerns, average similarity data obtained with PRaM tend to be reliable (Bijmolt & Wedel, 1995;Giordano et al, 2011;Verheyen et al, 2016).…”
Section: Comparisonmentioning
confidence: 99%
“…SpAM is not without disadvantages, however. Verheyen et al (2016) have formulated a number of caveats for the method. When the number of PRaM and SpAM participants is equated, the average SpAM similarity data tend to be less reliable.…”
Section: Comparisonmentioning
confidence: 99%
“…The spatial-arrangement method has been established as a fast and effective method for collecting similarity information Hout et al, 2013). However, it has previously been criticized for limiting the number of dimensions on which individuals can represent similarity (Verheyen, Voorspoels, Vanpaemel, & Storms, 2016). First, it is doubtful whether any of the current methods (e.g., spatial arrangement or exhaustive pairwise comparison) completely avoid this limitation .…”
Section: Discussionmentioning
confidence: 99%
“…Even though the method has been critiqued for having caveats in comparison to asking for a pairwise evaluation of distances (Verheyen et al 2016), it has been shown to produce good results in a fraction of the time required for pairwise evaluation or similar methods, such as triad tests (Hout and Goldinger 2016;Hout, Goldinger and Ferguson 2013). As the field evaluators had to drive over 4,000 kilometres in a few weeks to connect with all of the study participants, time was an essential component.…”
Section: Spatial Arrangementsmentioning
confidence: 99%